A Comparative Evaluation Of Fracture Resistance Of Endodontically Treated Teeth Using Conventional Glass Ionomer Cement, Resin Modified Glass Ionomer Cement, Nanohybrid Composite, Biodentin, Zirconomer, And Proroot Mineral Trioxide Aggregate As Intraorifi - Dubey, Astha; Varghese, Rana k; Gupta, Naveen Kumar; Jaiswal, Shreeya; Damodhar, Ippar Priyanka; Bishwal, Abhilasha (Journal of Neonatal Surgery, 2025)
Aim: This study primarily aims to evaluate the effectiveness of various intraorifice barrier materials in enhancing the fracture resistance of endodontically treated teeth. It focuses on identifying the material that offers the greatest structural reinforcement and reduces the likelihood of fractures, thereby contributing valuable insights into the material properties that impact the longevity and durability of treated teeth. By providing evidence-based findings, the study also seeks to support dental professionals in selecting the most suitable intraorifice barrier materials for improved clinical outcomes. Materials and methods: This in vitro study was conducted in the Department of Conservative Dentistry and Endodontics at New Horizon Dental College and Research Institute, Bilaspur, Chhattisgarh. A total of 105 freshly extracted human mandibular premolars, collected from patients aged 20–45 years, were used. Teeth were selected based on specific inclusion criteria—single-rooted premolars with single canals, extracted for periodontal reasons, and free from cracks, resorption, or abnormal root curvature. Ethical clearance was obtained prior to sample collection and experimentation. The teeth were cleaned, decoronated at the cementoenamel junction, and root canals were prepared using hand files up to size #20 followed by Protaper Universal rotary files till F3 size using the crown-down technique. Irrigation was done with sodium hypochlorite, EDTA, and distilled water, and the canals were obturated using F3 gutta-percha and AH Plus sealer. After sealing, the samples were incubated at 37°C for 8 hours. For all groups except the control, 3 mm of coronal gutta-percha was removed to make space for the intraorifice barrier Results: This study evaluated the fracture resistance of endodontically treated mandibular premolars restored with different intraorifice barrier materials, including Conventional Glass Ionomer Cement (GIC), Resin-Modified Glass Ionomer Cement (RMGIC), Zirconomer, Nanohybrid Composite, Biodentine, and Mineral Trioxide Aggregate (MTA). The primary objective was to determine the most effective material in reinforcing root canal-treated teeth and preventing fractures. The findings revealed that Zirconomer and Biodentine exhibited the highest fracture resistance, followed by Nanohybrid Composite. Conventional GIC and RMGIC provided moderate reinforcement, while MTA demonstrated the lowest resistance. The control group, without any intraorifice barrier, exhibited the weakest structural integrity, underscoring the necessity of using intraorifice barriers to enhance the mechanical strength of endodontically treated teeth. From a clinical perspective, Zirconomer and Biodentine are highly recommended for posterior teeth due to their superior strength and ability to withstand occlusal forces. Nanohybrid Composite serves as a viable option for anterior teeth, where esthetics is of a prime concern. conventional GIC and RMGIC offer the advantages of fluoride release, making them beneficial in cases where additional cariostatic effects are needed. MTA, despite its bioactive properties, showed limited mechanical reinforcement and may be best suited for applications, prioritizing biological sealing rather than fracture resistance. This study has certain limitations, as it was conducted in vitro, which does not fully replicate intraoral conditions such as occlusal forces, saliva exposure, and thermal changes. Additionally, the long-term durability and degradation of these materials over time were not assessed. Future research should focus on clinical trials under real-life conditions, along with the development of advanced bioactive materials that enhance both mechanical and biological properties Conclusion: In conclusion, this study confirms that intraorifice barriers play a crucial role in enhancing the fracture resistance of endodontically treated teeth. Zirconomer, Biodentine, and Nanohybrid Composite emerged as the most effective materials, significantly improving tooth strength and longevity. Their routine incorporation into endodontic treatment protocols is essential for ensuring long-term success and structural stability of treated teeth. Further research should continue exploring material innovations and assessing their long-term clinical effectiveness